Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0179758
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial angiogenesis is directed by RUNX1T1-regulated VEGFA, BMP4 and TGF-β2 expression

Abstract: Tissue angiogenesis is intimately regulated during embryogenesis and postnatal development. Defected angiogenesis contributes to aberrant development and is the main complication associated with ischemia-related diseases. We previously identified the increased expression of RUNX1T1 in umbilical cord blood-derived endothelial colony-forming cells (ECFCs) by gene expression microarray. However, the biological relevance of RUNX1T1 in endothelial lineage is not defined clearly. Here, we demonstrate RUNX1T1 regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…For example, Yafai et al reported that the upregulation of TGF-β2 inhibited the proliferation of retinal endothelial cells by enhancing the expression of Smad2 and Smad3 (18). Recently, it is reported that inhibition of TGF-β2/Samd contributed to alleviating proinflammation cytokines secretion (19) and decreasing endothelial angiogenic activities (20). Importantly, overexpression of TGF-β2 is associated with the levels of matrix metalloproteinase-2 (MMP2), MMP9, and VEGF in DR patients' vitreous samples (21), indicating that blocking the TGF-β2/Smad pathway might be a beneficial therapeutic approach for DR.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yafai et al reported that the upregulation of TGF-β2 inhibited the proliferation of retinal endothelial cells by enhancing the expression of Smad2 and Smad3 (18). Recently, it is reported that inhibition of TGF-β2/Samd contributed to alleviating proinflammation cytokines secretion (19) and decreasing endothelial angiogenic activities (20). Importantly, overexpression of TGF-β2 is associated with the levels of matrix metalloproteinase-2 (MMP2), MMP9, and VEGF in DR patients' vitreous samples (21), indicating that blocking the TGF-β2/Smad pathway might be a beneficial therapeutic approach for DR.…”
Section: Introductionmentioning
confidence: 99%
“…During early adipogenesis, Runx1t1 may act as an inhibitor of C/EBPβ contributing to its characteristically delayed activation, thereby block transcription of its downstream genes (such as PPARγ), inhibiting preadipocyte differentiation [32]. Serving as a common angiogenic driver for vaculogenesis and functionality of endothelial lineage cells, Runx1t1 direct angiogenesis by activating a number of angiogenic factors (VEGFA, BMP4, and TGF-β2) [33]. Runx1t1 also is demonstrated to regulate pancreas development by regulating pancreatic polypeptide and ghrelin expression [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few reports on the role of RUNX1T1 in adipogenesis, RUNX1T1 has been studied in-depth for its sophisticated functions since its initial identification [ 28 , 29 ]. In the formation of blood vessels, RUNX1T1 was confirmed to serve as an important angiogenic driver for vasculogenesis [ 30 ]. However, previous studies reported that RUNX1T1 has pleiotropic effects on fat development such as inhibiting CCAAT enhancer binding protein beta ( C/EBPβ ) activity during early adipogenesis and modulating preadipocyte differentiation through alternative splicing of RUNX1T1 [ 5 , 31 ].…”
Section: Discussionmentioning
confidence: 99%